Analisis SWOT Untuk Menentukan Strategi Kompetitif Pada Perusaahan Perkeretaapian: Studi Pada PT Kereta Api Indonesia (Persero) Daop 8 Surabaya - Efendi, Selfi Margareta; Indarwati, Tias Andarini (Seminar Nasional Manajemen, 2025)
Competition in the mass transportation industry in Indonesia has become increasingly intense in line with the growth of public mobility. PT Kereta Api Indonesia (Persero) Daop 8 Surabaya, as one of the operational centers of rail-based mass transportation in East Java, needs to implement effective and innovative strategies to respond to challenges and take advantage of internal and external opportunities in order to maintain and enhance its competitiveness. This study aims to analyze the internal and external factors of PT Kereta Api Indonesia (Persero) and to formulate appropriate competitive strategies through SWOT analysis. The research method applied in this study is descriptive. Data were collected through observation, interviews, and documentation. The results of this study indicate that PT Kereta Api Indonesia (Persero) is positioned in Quadrant I, which reflects significant growth potential. In this position, the company is expected to adopt an aggressive strategy to strengthen its growth in the transportation sector.